Conjunctive use of groundwater and surface water to reduce soil salinization in the Yinchuan Plain, North-West China - Li, Peiyue; Qian, Hui; Wu, Jianhua (International journal of water resources development, 2018)
Poor water resource management is an important factor in soil salinization in arid areas. In this study, the status of soil salinization and its controlling factors are summarized for the Yinchuan Plain, North-West China. The conjunctive use of surface water diverted from the Yellow River and groundwater abstracted from a shallow aquifer is proposed to alleviate soil salinization in the plain. Scenarios are designed and simulated to determine the optimal proportions at which groundwater should be exploited for irrigation in the three cities of the plain. Policies and suggestions regarding sustainable water resources and soil salinization research in the plain are recommended.